Effect of Stunning on Stress Responses and Quality of Farmed Bigeye Trevally (Caranx sexfasciatus) during Ice Storage - Anupama, T. K.; Binsi, P. K. (International Journal of Bio-resource and Stress Management, 2026)
A study was conducted during May–July, 2023 at ICAR-CIFT, Cochin, Kerala, India to evaluate the effect of the stunning by immersion in ice water slurry, on the flesh quality of Bigeye trevally (Caranx sexfaciatus) during ice storage. The changes in tissue stress/quality changes were monitored immediately after catch and during the shelf life of the fish. The major stress/quality parameters were escaping behaviour, muscular and vestibulo-ocular reflexes, pH at death, onset of rigor, and muscle pH, TVB-N, K-value, microbial, and sensory parameters during ice storage. The results indicated that the initial muscle pH was lower in conventional samples compared to fish stunned by ice immersion. The total volatile base nitrogen (TVB-N) increased significantly during storage and within an acceptable limit up to 21 days of storage for both conventional and stunned fish. K value increased considerably during storage, from 4.8% to 56.01% for conventional samples and 4.76% to 35.07% for stunned samples. Microbiologically, the conventional fish was rejected on the 17th day, and the stunned fish was rejected on the 21st day of storage. Sensory attributes were gradually diminished with the storage time which were in agreement with microbial counts. Based on the results of this study, the flesh quality of stunned big eye trevally could be maintained up to 21 days and conventional samples up to 17 days during ice storage.